PERLINDUNGAN HUKUM BAGI PEKERJA TERHADAP PEMBERIAN UPAH DI BAWAH UPAH MINIMUM - Chika Chika Agishintya; Siti Hajati Hoesin (Program Magister Ilmu Hukum Universitas Pancasila, 2021)
Wages are workers right that are received and expressed in the form of money as reward from the employers to the employee which is determined and paid according to an employment agreement or statutpry regulations. As a right for workers, the protection of workers against wages should be a concern. When workers are given wages below the minimum wage, it raises several problems. In some regulations, it has been regulated that employers must pay wages to their workers with minimum wage provisions. When workers have been employed and given wages below the minimum wage, it certainly does not reflect the existence of legal protection that accommodates the interests and welfare of these workers. The research method used is normative juridical, which is process to find a rule of law, legal principles and legal doctrines to answer the legal problems faced. The data analysis used is normative qualitative data analysis. Based on analysis results, information can be obtained that legal protection of wages for workers has been regulated in the legislation. However, its implementation is not optimal and there are still some deviations. Therefore, it is necessary to have a supervisory role by Dinas Tenaga Kerja on the implementation of the wage system in employment agreements so that the right of workers can be accommodated to the maximum